Genetic diversity of Roseroot (Rhodiola rosea L.) from Sweden, Greenland and Faroe Islands - Kylin, Madeleine (SLU/Plant Breeding and Biotechnology (until 121231), 2010)
Roseroot (R. rosea L.) has gained more attention the last years, mainly because of its phy-topharmacologic properties. Even though many reports in roseroot have been published, only a few articles are dealt with the genetic diversity. The Nordic Genetic Resource Center has collected Roseroot material from Sweden, Greenland and Faroe Islands under different expeditions. The samples were analysed to study the genetic diversity study. Such studies would facilitate The Nordic Genetic Re-source Center (NordGen) in conservation of roseroot in its gene bank. In this study, the roseroot materials collected in the NGB were analysed using two dif-ferent DNA marker methods, microsatellites (SSR) and inter simple sequence repeats (ISSR) for evaluating the genetic diversity. PCR products were separated on polyacryla-mide gels and developed with fast and sensitive silver staining. Gels were read manually with replications. Co-dominant and dominant marker data were analysed separately using POPGENE 1.32; and NTSYSpc 2.11. Four ISSR primers and four SSR primers were studied and resulted in 37 and 12 poly-morphic bands, respectively. Percentages of polymorphic bands for ISSR markers were for Sweden 83.78%, Greenland 94.59% and Faroe Islands 48.65%. Only two samples appear to be clonal material, the rest 89 samples are unique. No gender-specific or population-specific primers were found. Rosenrot (R.rosea L.) är en växt som fått mer intresse om sig de senaste åren, mestadels för dess fytofarmakologiska egenskaper. Även om många artiklar om rosenrot har blivit publicerade, så är det endast ett fåtal som handlar om dess genetiska diversitet. Nordiskt Genresurscenter har samlat in material från rosenrot ifrån Sverige, Grönland och Färöarna under olika expeditioner. Proven blev analyserade för att studera den genetiska diversiteten. Resultat från en genetisk diversitetsstudie kan hjälpa Nordiskt Genresurscen-ter i deras bevarandesyfte för sin genbank. I den här studien har insamlat material från NordGen blivit analyserade av två ...